Use of a Porous Polyethylene Lid Spacer for Management of Eyelid Retraction in Patients with Boston Type II Keratoprosthesis. (August 2013) - Sivaraman, Kavitha R.; Aakalu, Vinay K.; Sajja, Kiran; Cortina, Maria Soledad; de la Cruz, Jose; Setabutr, Pete
Abstract Purpose: To report a novel application of a porous polyethylene implant for lid stabilization and management of eyelid retraction in a patient with an exposed Boston Keratoprosthesis Type II. Methods: A 54-year-old woman with a history of mucous membrane pemphigoid and failed penetrating keratoplasty of the left eye underwent implantation of a Boston Keratoprosthesis (KPro) Type II along with permanent surgical fusion of the upper and lower lids of the left eye in January 2010. At one month follow-up, significant retraction of the lower lid around the inferior margin of the optic was noted, resulting in partial exposure of the keratoprosthesis. The patient subsequently underwent left lower eyelid reconstruction with a porous polyethylene implant to ensure coverage and stability of the KPro. Results: Eyelid reconstruction using a porous polyethylene implant resulted in stable retention of the KPro Type II for over 2 years. Conclusion: In patients with Boston KPro Type II in the setting of severe cicatrizing ocular surface disease, the use of a porous polyethylene implant during eyelid reconstruction around the KPro optic may aid in maintaining eyelid integrity and improving KPro stability and longevity.